Probing for congenital nasolacrimal duct obstruction - Petris, Carisa (Cochrane Database Syst Rev, 2017)
BACKGROUND: Congenital nasolacrimal duct obstruction (NLDO) is a common condition causing excessive tearing in the first year of life. Infants present with excessive tearing or mucoid discharge from the eyes due to blockage of the nasolacrimal duct system, which can result in maceration of the skin of the eyelids and local infections, such as conjunctivitis, that may require antibiotics. The incidence of nasolacrimal duct obstruction in early childhood ranges from 5% to 20% and often resolves without surgery. Treatment options for this condition are either conservative therapy, including observation (or deferred probing), massage of the lacrimal sac and antibiotics, or probing the nasolacrimal duct to open the membranous obstruction at the distal nasolacrimal duct. Probing may be performed without anesthesia in the office setting or under general anesthesia in the operating room. Probing may serve to resolve the symptoms by opening the membranous obstruction; however, it may not be successful if the obstruction is due to a bony protrusion of the inferior turbinate into the nasolacrimal duct or when the duct is edematous (swollen) due to infection such as dacryocystitis. Additionally, potential complications with probing include creation of a false passage and injury to the nasolacrimal duct, canaliculi and puncta, bleeding, laryngospasm, or aspiration. OBJECTIVES: To assess the effects of probing for congenital nasolacrimal duct obstruction. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), which contains the Cochrane Eyes and Vision Trials Register (2016, Issue 8); MEDLINE Ovid (1946 to 30 August 2016); Embase.com (1947 to 30 August 2016); PubMed (1948 to 30 August 2016); LILACS (Latin American and Caribbean Health Sciences Literature Database; 1982 to 30 August 2016), the metaRegister of Controlled Trials (mRCT) (www.controlled‐trials.com), last searched 14 August 2014; ClinicalTrials.gov (www.clinicaltrials.gov), searched 30 August 2016; and the WHO International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en), searched 30 August 2016. We did not use any date or language restrictions in the electronic searches for trials. SELECTION CRITERIA: We included randomized controlled trials (RCTs) that compared probing (office‐based or hospital‐based under general anesthesia) versus no (or deferred) probing or other interventions (observation alone, antibiotic drops only, or antibiotic drops plus massage of the nasolacrimal duct). We did not include studies that compared different probing techniques or probing compared with other surgical procedures. We included studies in children aged three weeks to four years who may have presented with tearing and conjunctivitis. DATA COLLECTION AND ANALYSIS: Two review authors independently screened studies for inclusion and independently extracted data and assessed risk of bias for the included studies. We analyzed data using Review Manager software and evaluated the certainty of the evidence using GRADE. MAIN RESULTS: We identified two RCTs and no ongoing studies; one of the included RCTs was registered. The studies reported on 303 eyes of 242 participants who had unilateral or bilateral congenital nasolacrimal duct obstruction. For both included studies, the interventions compared were immediate office‐based probing to remove the duct obstruction versus deferred probing, if needed, after 6 months of observation or once the child reached a certain age. The primary outcome of the review, treatment success at 6 months, was reported partially in one study. Treatment success was not reported at this time point for all children in the immediate probing group; however, 77 of 117 (66%) eyes randomized to deferred probing had resolved without surgery 6 months after randomization and 40 (34%) eyes did not resolve without probing. For children who had unilateral NLDO, those randomized to immediate probing had treatment success more often than those who were randomized to deferred probing (RR 1.41, 95% CI 1.12 to 1.78; 163 children; moderate‐certainty evidence). Treatment success for all children was assessed in the study at age 18 months; as an ad hoc analysis in the included study, results were presented separately for children with unilateral and bilateral NLDO (RR 1.13, 95% CI 0.99 to 1.28 and RR 0.86, 95% CI 0.70 to 1.06, respectively; very low‐certainty evidence). In the other small study (26 eyes of 22 children), more eyes that received immediate probing were cured within one month after surgery compared with eyes that were randomized to deferred probing and analyzed at age 15 months (RR 2.56, 95% CI 1.16 to 5.64). We considered the evidence to be low‐certainty due to imprecision from the small study size and risk of bias concerns due to attrition bias. One study reported on the number of children that required reoperation; however, these data were reported only for immediate probing group. Nine percent of children with unilateral NLDO and 13% with bilateral NLDO required secondary procedures. One study reported cost‐effectiveness of immediate probing versus deferred probing. The mean cost of treatment for immediate probing was less than for deferred probing; however, there is uncertainty as to whether there is a true cost difference (mean difference USD ‐139, 95% CI USD −377 to 94; moderate‐certainty evidence). Reported complications of the treatment were not serious. One study reported that there were no complications for any surgery and no serious adverse events, while the other study reported that bleeding from the punctum occurred in 20% of all probings. AUTHORS' CONCLUSIONS: The effects and costs of immediate versus deferred probing for NLDO are uncertain. Children who have unilateral NLDO may have better success from immediate office probing, though few children have participated in these trials, and investigators examined outcomes at disparate time points. Determining whether to perform the procedure and its optimal timing will require additional studies with greater power and larger, well‐run clinical trials to help our understanding of the comparison.